ANALISIS PENGARUH PENDAPATAN, FLEXIBLE WORKING, DAN RELIGIUSITAS TERHADAP MINAT GENERASI Z DALAM GIG ECONOMY - Prakoso, Bayu Dwi; Anggraeni, Ika Khusnia (Islamic Economics and finance in Focus, 2023)
The job market has changed due to globalization which has initiated a new job market sector, namely the gig economy. Gig worker in Indonesia in Indonesia have increased every year which is dominated by generation z. This happened due to several factors. This study uses income, flexible working variables to determine whether these variables affect interest generation z in gig economy. In this study, data were collected through questionnaires with purposive sampling. Respondents in this study amounted to 100 respondents who have interest in gig economy. The analysis technique used is multiple linear regression analysis. The results of this study indicate that the variables of income and flexible working have a positive and significant influence on interest generation z. Meanwhile, the religiousity variable has a positive but not significant effect on interest generation z